Case 3857: Acmaeodera brevipes Kiesenwetter, 1858 (Insecta, Coleoptera): proposed precedence over Acmaeodera cuprifera Laporte & Gory, 1835. - Kwast, Tom (Bulletin of Zoological Nomenclature, 2021)
<a title="https://bioone.org/journals/the-bulletin-of-zoological-nomenclature/volume-78/issue-2/bzn.v78.a022/Notice-of-New-Applications-to-the-Commission-Case-38533857/10.21805/bzn.v78.a022.full" href="https://bioone.org/journals/the-bulletin-of-zoological-nomenclature/volume-78/issue-2/bzn.v78.a022/Notice-of-New-Applications-to-the-Commission-Case-38533857/10.21805/bzn.v78.a022.full">Noticed in BZN 78: 68 on 30 August 2021 Closure in BZN 81: 181 on 31 December 2024